HIERARCHY OF DIFFICULTY IN SECOND LANGUAGE LEARNING ON RIGWE LEARNERS OF ENGLISH: WAY OUT - AMALE , Felix Aishe; Atinga, Larai Azuwo Adamu; Isa, Saratu Shuaibu (International Journal of Arts, Languages, Linguistics and Literary Studies, 2023)
The learning of a second language could be very frustrating, especially when the structural rudiments of the Native Language are different from the ones in the Target Language. There a lot of works on the hierarchy of difficulty in learning second languages like most developed languages in the world like English, French, German and others. However, little has been done on the hierarchy of difficulty Rigwe learners of the English language are likely to encounter. And this is gap this study sets out to fill. The study aimed at investigating the hierarchy of difficulty in second language learning on Rigwe learners of English, and to proffer possible solutions to the difficulties observed in the course of the study. Norm Chomsky’ (1981) X-bar module of the Principles and Parameters Theory was adopted as the theoretical anchorage for the study. The Rigwe data for this study were derived from two sources: first, the recording of expressions made by people in social and informal gatherings, Rigwe New Testament Bible and also from “How to Read and Write Rigwe by Gya. Likewise, some relevant English structures were borrowed from the English syntax materials. Based on the results of the study, gender pronoun falls under the hierarchy of difficulty split because the pronoun “áà”  is used in the source language as she, he and it. Possession is not shown in Rigwe using ‘s’ but ni which is equivalent to “of” genitive or through noun-noun construction. This constitutes level 2 (underdifferentiation) of hierarchy of difficulty. The differences in the use of adjective and determiners falls under level 3 (reinterpretation) of hierarchy of difficulty because both adjective and determiner exist in the mother tongue but need to be given new shape in the TL. Lastly, the area of difficulty observed in the use of negation is that Rigwe sentences can have two negative markers: one coming at the beginning of the sentence, while the other one at the end of the sentence. A Rigwe learner of the English language would have to coalesce the two items to become one in the target language. This falls under level I (coalescence). In conclusion, teachers of the English language in Rigwe community must learn to identify each difficulty and design a way to help learners with the appropriate structures in the target language (English)